Close your eyes ebook - Robotham, Michael (Joseph O'Loughlin, 2016)
When a former student bungles a murder investigation, clinical psychologist Joseph O'Loughlin steps in to face a ruthless killer. A mother and her teenage daughter are found murdered in a remote coastal home, one defiled by multiple stab wounds and the other posed like Sleeping Beauty waiting for her prince. Joe O'Loughlin is drawn into the investigation when a former student, trading on Joe's reputation by calling himself "the Mindhunter," jeopardizes the police inquiry by leaking details to the media and stirring up public anger. Joe discovers a link between the farmhouse murders and a series of vicious attacks in which the victims are choked unconscious and brutally scarred. Now, Joe must stop a ruthless and brash criminal who has apparently graduated to murder. Much to his surprise, he is ably assisted by his eldest daughter, now a keen and courageous observer of her own right. Together they must track and catch a hunter who seems to anticipates every move they make. #1 International Bestseller " Close Your Eyes : the best Michael Robotham novel yet . . . impossible to put down." — Stephen King